#TITLE_ALTERNATIVE# - ASHARI (NIM 13703025), DHANIAL
Turbine blade is one of the components of aero engine that will be exposed on high temperature. Superalloy materials mostly used for turbine blade's material, because it has good strength at elevated temperature. One of the superalloys used is SRR 99. It is nickel based superalloys and is single crystal. However, this material will undergo a change on micro structure and mechanical properties (hardness) when it is exposed at high temperature. This research will be focused on the effect of overheat temperature on micro structure of SRR 99. The overheat temperature will be determined in four treatment conditions. The first heating is on temperature 950oC, second heating on temperature 1050oC, third heating on temperature 1150oC, and last heating on temperature 1250oC. In every treatment state, the speciment will be heated for 10 minutes using furnace and then air cooled. The effect of heat treatment to turbine blade's material can be seen on the changing of micro structure and hardness value, than it will be compared by the turbine blade's material early condition. Early micro structure achieve from root of turbine blade before heating. The result from treatment I, there is increasing on size of y' particles that caused by diffusion the substance of y' particles from the matrix y and there is no change in hardness value, which is 340 HV. The result from treatment II and III, there is increasing on size of y' particles that caused by Gibbs-Thompson effect, for treatment II, there is no change in hardness value, it is 340 + 6 HV, whereas for treatment III, there is a change in hardness value. It becomes 330 + 6 HV. And the result from treatment IV, there is dissolve of y' particle to y' matrix, and there is change in hardness value. It becomes 316 + 6 HV.